Oxidation effects on spark plasma sintering of molybdenum nanopowders. Issue 2 (9th November 2018) - Lee, Geuntak; Manière, Charles; McKittrick, Joanna; Gattuso, Anthony; Back, Christina; Olevsky, Eugene A.
Abstract: Surface‐oxidized molybdenum nanopowders are compacted by spark plasma sintering (SPS). The oxide impurity behavior is analyzed under various sintering temperatures. The densification mechanism of the nanopowders with a melted oxide phase is identified in situ by regression analysis of the experimental data on the temperature‐dependent porosity change and on the SPS multistep pressure dilatometry. To increase the density of the compacted pellets, the nanopowders with the oxide phase are consolidated by SPS using the two in situ oxide removal methods: carbothermic reduction and particle surface cleaning by the electric current flow through the powders. The advantages and disadvantages of these methods in terms of the density, grain size, and mechanical properties of the final products are discussed.